God and Self in the Confessional Novel - Sykes, Jr., John D. (Springer International Publishing, 2018)
God and Self in the Confessional Novel explores the question: what happened to the theological practice of confession when it entered the modern novel? Beginning with the premise that guilt remains a universal human concern, this book considers confession via the classic confessional texts of Augustine and Rousseau. Employing this framework, John D. Sykes, Jr. examines Goethe's The Sorrows of Young Werther, Dostoevsky's Notes from Underground, Percy's Lancelot, and McEwan's Atonement to investigate the evolution of confession and guilt in literature from the eighteenth century to the early twenty-first century.